Efektivitas Metode Tilawati dalam Meningkatkan Kefasihan Membaca Al-Qu’an pada Siswa Kelas 1 di SMP Muhammadiyah 1 Medan - Muhammad Firdous Saun (EL-EMIR Institute, 2026)
This study aims to determine the effectiveness of the Tilawati method in improving Qur'an reading fluency in first-grade junior high school students. The Tilawati method is a Qur'an learning method that integrates classical and individual approaches with the use of Rost songs, thus helping students read fluently, fluently, and correctly according to Tajweed rules. This study used a quantitative approach with a pre-experimental design using a one-group pretest-posttest model. The study subjects consisted of 30 first-grade junior high school students at one school. Data collection techniques were carried out through Qur'an reading tests given before (pretest) and after (posttest) the application of the Tilawati method, supported by observations during the learning process. The data obtained were analyzed using descriptive and inferential statistical tests to determine differences in results before and after treatment. The results showed a significant increase in students' Qur'an reading fluency after the application of the Tilawati method. This can be seen from the increase in students' average scores from pretest to posttest, as well as positive changes in fluency, Tajweed accuracy, and pronunciation of letters. Furthermore, the Tilawati method also increases students' motivation to learn due to its engaging and interactive presentation. Therefore, it can be concluded that the Tilawati method is effective in improving Quranic recitation fluency in first-grade junior high school students.